Smoking during pregnancy and fetal brain development - Ekblad, Mikael (Annales Universitatis Turkuensis D 1065, 2013)
Background: Although the knowledge of adverse effects of smoking during pregnancy has increased in recent years, more research is needed to gain a better understanding of the effects of smoking during pregnancy. Smoking exposure is the most common preventable factor that causes adverse pregnancy outcomes. Aims and Methods: First, data on smoking habits during pregnancy from the Nordic Medical Birth Registers was used to study the national differences in trends of smoking during pregnancy. Second, the effects of prenatal smoking exposure on fetal brain development, assessed by brain MRI at term age, were studied by using data from the multidisciplinary PIPARI Study consisting of a 6-year cohort of VLBW/VLGA infants (n = 232, of which 18.1% were exposed to prenatal smoking) born in Turku University Hospital, Finland. Third, the effects of prenatal smoking exposure on psychiatric morbidity and use of psychotropic medication were studied in a cohort of children born from 1987–1989 in Finland (n = 175,869, of which 15.3% were exposed). The data used were obtained from population-based longitudinal registers from the National Institute of Health and Welfare, the Statistics Finland, and the Finnish Social Insurance Institution. Results: Smoking rates during pregnancy differed considerably between the countries. Smoking rates were highest among teenagers and women with lower socioeconomic positions. The smoking prevalence was found to be increasing among teenagers in both Finland and Norway. Prenatal smoking exposure was associated with smaller frontal lobe and cerebellar volumes in preterm infants. A clear association was found between prenatal smoking exposure and psychiatric morbidity treated with specialized hospital care and the use of various psychotropic medications. Conclusions: Prenatal smoking exposure had adverse effects on fetal brain development. These effects might explain part of the association found between smoking exposure and psychiatric problems in later life. Our study suggests that prenatal smoking exposure is linked with both mild and severe psychiatric problems. This study emphasizes the importance of efforts to reduce smoking during pregnancy.

Raskaudenaikainen tupakointi ja keskushermoston kehitys Tausta: Vaikka tietoisuus raskaudenaikaisen tupakoinnin haitoista on lisääntynyt viime vuosina, lisätutkimukset aiheesta ovat tarpeen. Tupakointi on yleisin ehkäistävissä oleva raskauskomplikaatioita ja lapselle myöhempiä haittoja aiheuttava tekijä. Tavoitteet ja menetelmät: Tutkimme Pohjoismaiden tupakoinnin trendien eroja Pohjoismaisten syntymärekisterien tiedoilla raskaudenaikaisesta tupakoinnista. Raskaudenaikaisen tupakka-altistuksen yhteyttä keskosten aivojen kehitykseen tutkittiin aivojen MRI-kuvauksella lasketussa ajassa. Aineisto koostui PIPARItutkimuksen 6-vuotiskohortin pikkukeskosista (n = 232, joista 18,1 % altistui tupakoinnille), jotka syntyivät Turun yliopistollisessa keskussairaalassa. Lisäksi tutkimme tupakka-altistuksen yhteyttä vuosina 1987–1989 syntyneiden nuorten (n = 175,869, joista 15,3 % altistui) psykiatriseen sairastuvuuteen ja psykiatristen lääkkeiden käyttöön. Aineisto muodostettiin Terveyden ja hyvinvoinnin laitoksen, Tilastokeskuksen ja Kansaneläkelaitoksen tiedoista. Tulokset: Raskaudenaikaisen tupakoinnin esiintyvyys erosi selkeästi Pohjoismaiden välillä. Yleisintä tupakointi oli teineillä ja alhaisen sosiaalisen taustan omaavilla naisilla. Huolestuttavinta oli, että teinien tupakointi on lisääntynyt Suomessa ja Norjassa. Raskaudenaikainen tupakointi oli yhteydessä pienempiin etuaivolohko- ja pikkuaivotilavuuksiin pikkukeskosilla. Löysimme myös selkeän yhteyden tupakka-altistuksen ja nuorten psykiatrisen sairastuvuuden ja psykiatristen lääkkeiden käytön välillä. Päätelmät: Raskaudenaikaisella tupakka-altistuksella on selkeitä haittoja sikiön aivojen kehitykseen. Nämä löydökset voivat selittää osan löydetystä yhteydestä tupakka-altistuksen ja psykiatrisen sairastuvuuden välillä. Tutkimuksemme perusteella tupakka-altistus on yhteydessä lieviin ja vaikeisiin psykiatrisiin häiriöihin. Tutkimustuloksemme korostavat, että on tärkeää ehkäistä ja vähentää raskaudenaikaista tupakointia.